(untitled) (Baghdad Science Journal, 2025)
The present work involved preparation of new hetro cyclic polyacrylamides (1-9) using reaction of polyacryloyl chloride with 2-aminobenzothiazole which prepeard by thiocyanogen method in the presence of a suitable solvent and amount tri ethyl amine (Et3N) with heating. The structure confirmation of polymers were proved using FT-IR,1H-NMR,C13NMR and UV spectroscopy.Other physical properties including softening and melting points, and solubility of the polymers were also measured.